Application of Quality Function Deployment in Improving Service Quality at PT. Yamaha Indonesia Motor Manufacturing - NUGRAHA, Eka; NUGROHO, Rian Joko; NOORMAYASARI, Widiya; SUHARDI, Agatha Rinta (International Journal of Environmental, Sustainability, and Social Science, 2025)
The study addresses the question, “How does the application of QFD help YIMM enhance the service quality of its motorcycle products in Indonesia?”. A mixed-methods approach was employed, using surveys and interviews to collect data from YIMM customers and management. Data were analyzed using a Likert scale and statistical software to identify key customer requirements. The findings indicate that the attributes of Service Ability, Conformance, and Perceived Quality are primary factors in customer satisfaction with Yamaha products, while the Aesthetic attribute requires improvement. This study fills a gap in the literature by examining QFD as a quality improvement tool within Indonesia’s automotive industry, specifically in the automatic motorcycle segment. The application of QFD at YIMM has effectively enhanced service quality in line with customer expectations. However, improvements in product aesthetics could further strengthen YIMM’s competitive position in the market.